2010
DOI: 10.1073/pnas.1000988107
|View full text |Cite
|
Sign up to set email alerts
|

Insights into protein folding mechanisms from large scale analysis of mutational effects

Abstract: Protein folding mechanisms are probed experimentally using single-point mutant perturbations. The relative effects on the folding (ϕ-values) and unfolding (1 − ϕ) rates are used to infer the detailed structure of the transition-state ensemble (TSE). Here we analyze kinetic data on >800 mutations carried out for 24 proteins with simple kinetic behavior. We find two surprising results: (i) all mutant effects are described by the equation: ΔΔG ‡ unfold ¼ 0.76ΔΔG eq AE 1.8 kJ∕mol. Therefore all data are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 39 publications
16
115
1
Order By: Relevance
“…1. For a reliable ϕ-value analysis ΔΔG 0 has to be sufficiently large (>5-7 kJ∕mol) (8,11). Table 1 shows that all thioxo-peptide bonds in the helical region except thioxo Ala4 fulfill this criterion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. For a reliable ϕ-value analysis ΔΔG 0 has to be sufficiently large (>5-7 kJ∕mol) (8,11). Table 1 shows that all thioxo-peptide bonds in the helical region except thioxo Ala4 fulfill this criterion.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been successfully applied to characterize transition states for protein folding (1,2), for proteinprotein interactions (3)(4)(5) and for conformational changes in folded proteins (6). Protein folding transition states were shown to have native-like topology in the whole protein or in major parts of the structure (7)(8)(9) and it is commonly assumed that this includes the presence of native-like secondary structure (10,11). Because site-directed mutagenesis can only modify amino acid side chains, it is still unclear at which stage of a folding reaction backbone hydrogen bonds in secondary structure elements are formed.…”
mentioning
confidence: 99%
“…S5). ϕ f -Values of about 0.3 are also found for the effect of most mutations on folding of small, single-domain proteins when only reliable ϕ f -values are considered (36,40). 5.…”
Section: Local Effects Of Capping Motifs and Amino Acid Sequence On Hmentioning
confidence: 97%
“…Comparative analysis of nearly all Φ-values reported to date revealed that the α-value in protein folding is robust and, for nearly all proteins investigated, α is about 0.36 (30). The mutational work reported in Table 1 is an opportunity to apply the LFER to the recognition reaction between an IDP and its physiological partner (Fig.…”
Section: An Ordered Transition State As a Signature Of Geometrical Prmentioning
confidence: 98%